Substance use–related continuing education course objectives: Alignment with professional competencies. Issue 1 (1st December 2022) - Finnell, Deborah S.; Soltis-Jarrett, Victoria; Bratberg, Jeffrey; Muzyk, Andrew; Liu, Yifei; Edens, Ellen; Seale, J. Paul; Mattingly, Jill; Schnurman, Kristen; Osborne-Leute, Victoria; Zweben, Allen; Cary, Ann; et al.
Abstract: Background : Novel educational efforts are needed to prepare the current and future interprofessional health care workforce to address the range of substance use–related health problems. A 6-module massive open online course (MOOC) was developed to provide education to health professionals of various disciplines on the fundamentals of substance use–related treatment. The purpose of this project was to match course objectives to substance use–related competencies for 5 disciplines: nurses, pharmacists, physicians, physician assistants (PA), and social workers. Methods : Content expert raters within each discipline determined what Association for Multidisciplinary Education and Research in Substance use and Addiction (AMERSA) core competencies were matched to each objective for the 6 modules of the MOOC. The number of objectives across the 6 modules was summated. Results : All nursing and social work competencies were mapped to the course objectives. For physicians, PAs, and pharmacists, the proportions of knowledge-based competencies that mapped to the course objective were 58%, 76%, and 80%, respectively, and proportions of skill-based competencies that mapped to the course objective were 88%, 83%, and 75%, respectively. For those 3 groups, 100% of attitude-based competencies mapped to the course objective. Conclusions : The competency-based mapping with the MOOC objectives supports the interprofessional design of the course and discipline-specific competencies needed to promote the best outcomes for patients.